2011
DOI: 10.1007/s10533-011-9681-0
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric methane uptake by tropical montane forest soils and the contribution of organic layers

Abstract: Microbial oxidation in aerobic soils is the primary biotic sink for atmospheric methane (CH 4 ), a powerful greenhouse gas. Although tropical forest soils are estimated to globally account for about 28% of annual soil CH 4 consumption (6.2 Tg CH 4 year -1 ), limited data are available on CH 4 exchange from tropical montane forests. We present the results of an extensive study on CH 4 exchange from tropical montane forest soils along an elevation gradient (1,000, 2,000, 3,000 m) at different topographic positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 48 publications
10
48
2
Order By: Relevance
“…These rates (kg CH 4 -C ha −1 year −1 ) are comparable to those measured in the southern Ecuadorian Andes (−5.9;Wolf et al, 2012), Japanese larch (Larix kaempferi Sarg.) forest on volcanic soils (− 6.3; Ueyama et al, 2012), beech forest (Fagus sylvatica) in New Zealand (− 7.9; Price et al, 2004), desert steppe of Inner Mongolia (− 7.9;Tang et al, 2013), and deciduous forests in northwestern Pennsylvania (−8.9;Bowden et al, 2000).…”
Section: Riparian Forests As Strong Ch 4 Sinkssupporting
confidence: 80%
“…These rates (kg CH 4 -C ha −1 year −1 ) are comparable to those measured in the southern Ecuadorian Andes (−5.9;Wolf et al, 2012), Japanese larch (Larix kaempferi Sarg.) forest on volcanic soils (− 6.3; Ueyama et al, 2012), beech forest (Fagus sylvatica) in New Zealand (− 7.9; Price et al, 2004), desert steppe of Inner Mongolia (− 7.9;Tang et al, 2013), and deciduous forests in northwestern Pennsylvania (−8.9;Bowden et al, 2000).…”
Section: Riparian Forests As Strong Ch 4 Sinkssupporting
confidence: 80%
“…Consistent trace GHG emissions from tree stem bases have also been observed in temperate upland forests (Pitz & Megonigal, 2017;Wang et al, 2016;Warner, Villarreal, McWilliams, Inamdar, & Vargas, 2017) and suggest that GHGs may be produced within the tree stem (Covey, Wood, Warren, Lee, & Bradford, 2012;Wang et al, 2016), or that the transport of trace GHGs through tree stems bypassed the oxygenated surface horizons, where the majority of CH 4 oxidation (Teh, Silver, & Conrad, 2005;Wolf, Flessa, & Veldkamp, 2012) and more complete denitrification (Koehler et al, 2012;Wieder et al, 2011) occurs. Hence, the production or transport of trace GHGs in tree stems could represent a large and currently unac- in temperate upland trees (Machacova et al, 2013;Pitz, Megonigal, Chang, & Szlavecz, 2018;Wang et al, 2016;Wen et al, 2017), and our tree stem CH 4 fluxes also lie within the range of tropical peatland forests (17-185 µg m −2 hr −1 ; Pangala et al, 2013).…”
Section: Trace Ghg Fluxes From Tree Stemsmentioning
confidence: 65%
“…3.4) across landscapes as evidence for N-limited CH 4 uptake. Indications of N-limited CH 4 uptake have been reported for tropical forests in Panama (Veldkamp et al, 2013) and Ecuador (Wolf et al, 2012), but this is the first time that it was observed on a landscape scale in the tropics. Furthermore, the positive correlations of annual soil CH 4 fluxes from the reference land-use types with exchangeable Al within each landscape reflected the lower CH 4 uptake measured at sites with more exchangeable Al in the soil.…”
Section: Co 2 and Ch 4 Fluxes From The Reference Land-use Typesmentioning
confidence: 78%